Pengaruh Citra Merek dan Kredibilitas Terhadap Loyalitas Pelanggan dengan Sertifikasi Halal Sebagai Variabel Moderating Pada Produk Frozen Food - Selamet Eko Kristanto; Trian Zulhadi; Syahpawi Syahpawi (ISLAMIC BUSINESS and FINANCE, 2023)
Abstract The purpose of this study is to determine Brand Image and Credibility on Customer Loyalty with Halal Certification as a moderating variable. The approach used in this study is an associative approach. The sampling technique used in this study is the saturated sample technique found in non-probability sampling, namely the sampling technique when all members of the population are used as a sample of 118 respondents. Data collection was carried out by distributing questionnaires to all Resellers consisting of Agents, Wholesalers and Retailers who partnered with CV distributors. Pekanbaru's New Taste. The data analysis technique used in this study is the classical assumption test, multiple linear regression, t test, f test, coefficient of determination and moderated regression analysis (MRA) using the IBM SPSS version 23 program. The results of this study indicate that brand image partially influences significant to Customer Loyalty and Credibility has a significant effect on Customer Loyalty. Simultaneously Halal Certification as a moderating variable is able to moderate the relationship between Brand Image and Customer Loyalty. Halal Certification as a moderating variable is not able to influence the relationship between Credibility and Customer Loyalty.Key words: Brand Image, Credibility, Halal Certification, Customer Loyalty